1999
DOI: 10.1046/j.1365-2672.1999.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat resistance of Lactobacillus spp. isolated from Cheddar cheese

Abstract: K .N . J O RD AN A ND T. M . C OG A N. 1999. Mesophilic Lactobacillus spp. are the dominant organisms in mature Cheddar cheese. The heat resistance of broth grown cultures of Lactobacillus plantarum DPC1919 at temperatures between 50 and 57·5°C, Lact. plantarum DPC2102 at temperatures between 48 and 56°C and Lact. paracasei DPC2103 at temperatures between 50 and 67·5°C was determined. The z-values for Lact. plantarum DPC1919, Lact. plantarum DPC2102 and Lact. paracasei DPC2103 were 6·7°C, 6·2°C and 5·3°C, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 12 publications
6
49
1
Order By: Relevance
“…Moreover, higher D values between 63 and 80°C, which were mostly obtained from experiments using milk and were available only in fewer numbers than those at lower temperature, might also contribute to the lower slope of the regression. The estimated z value of 6.5°C, when the D values at the temperature range of our study (50 and 63°C) were used, corresponded more or less to the reported z values of vegetative cells, which are between 5 and 7°C (41,61,62).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, higher D values between 63 and 80°C, which were mostly obtained from experiments using milk and were available only in fewer numbers than those at lower temperature, might also contribute to the lower slope of the regression. The estimated z value of 6.5°C, when the D values at the temperature range of our study (50 and 63°C) were used, corresponded more or less to the reported z values of vegetative cells, which are between 5 and 7°C (41,61,62).…”
Section: Discussionsupporting
confidence: 73%
“…Survival of all L. paracasei strains during heating supports the idea that one source of NSLAB in cheese should be raw milk as also suggested by Jordan and Cogan (1999). L. paracasei subsp.…”
Section: Survival During Heatingsupporting
confidence: 52%
“…Some species of Lactobacillus have also been shown to have the potential to survive pasteurization. However, their resistance depends on genetic variations among strains, the physiological status of the cells and other environmental factors [26,27]. Therefore, it is not surprising that these groups of bacteria (specially Clostridium and Enterococcus) were isolated more frequently from samples comprising fish or meat (even if they were cooked) as contamination with this faecal species would have occurred more frequently in slaughterhouse conditions compared to contamination in the environment.…”
Section: Resultsmentioning
confidence: 99%